Analisis Pengaruh Product Placement Pada Produk Kopi Luwak Dalam Sinetron “Ikatan Cinta” Terhadap Brand Awareness Melalui Brand Recall - Winda Nur Fauzia; Miftahul Huda (Fakultas Ekonomi Universitas Kadiri, 2022)
Marketing can be done through electronic media, one of which is TV. What is currently seen is that a promotion is carried out using a product placement strategy. The purpose of this study was to determine the effect of brand recall which is used as an intervening variable in the relationship between Kopi Luwak product placement in the soap opera, the bond of love to brand awareness. The number of samples in this study as many as 160 respondents who became viewers of the soap opera bond of love from teenagers to adults and domiciled in Pasuruan City. In this study using path analysis as an analytical technique. After doing this research, the results show that product placement has a positive and significant effect on brand awareness, product placement also has a significant positive effect on brand recall and brand recall is not able to function as an intervening variable between the relationship between product placement and brand awareness